Iron Supplementation Confers Protection on Disease Severity in Dextran Sodium Sulfate (DSS)-Induced Colitis in Rats (OR15-05-19). (13th June 2019) - Bries, Amanda; Derscheid, Rachel; Curry, Paige; Webb, Joe; Meier, Olivia; Johnson, Casey; Ferrere, Taylor; Rowling, Matthew; Reddy, Manju
Abstract: Objectives: Koji iron, enriched with FeSO4 (Ultimine ® ; ULT), is a novel source of supplemental iron. Previously, we reported ULT had similar absorption as ferrous sulfate (FeSO4 ), while resulting in less reported adverse effects in women. Iron deficiency anemia is a common manifestation of inflammatory bowel disease (IBD) due to malabsorption and gastrointestinal (GI) bleeding. Therefore, the objective of our study was to identify the efficacy of 2 forms of iron supplementation on impaired GI integrity and anemia caused by dextran sulfate sodium (DSS)-induced colitis. Methods: Six wk old Sprague Dawley rats ( n  = 40) were randomly assigned to one of four treatment groups ( n  = 10/group): 1) Control with no DSS; 2) Control + DSS only (Nfe); 3) DSS + ULT; 4) DSS + FeSO4 . Animals were maintained on the AIN-93 G diets for 7 d. Colitis was induced by administering fresh 3.5% (w/v) DSS ad lib throughout the study. Daily iron supplementation (6 mg Fe/kg BW) was provided in a pulverized treat, and disease activity indices were observed (gross bleeding, stool consistency and weight loss). Histological scoring of colonic ulcerations, inflammation and grade were assessed. Iron status indicators and liver hepcidin were detected using ELISA and qRT-PCR, respectively. Results: The severity score of IBD was significantly higher in the animals without iron supplementation than those treated with iron ( P  <   0.0001). Moreover, iron supplementation protected against diminished hemoglobin and hematocrit levels as a result of DSS treatment ( P  = 0.001 and P  = 0.03, respectively); whereas, these parameters were not significantly (NS) different between ULT and FeSO4. Improvement was found with post mortem disease score of DSS-induced rats with ULT compared to FeSO4 and Nfe by 14% and 39%, respectively (NS). Compared to healthy controls, FeSO4 resulted in a 3.5-fold increase in liver hepcidin gene expression, whereas ULT caused no change. Conclusions: The results of this study highlight the beneficial effects iron supplementation has on the disease activity evoked by severe GI inflammation. Furthermore, this data suggests ULT attenuates the progression of IBD by supporting iron homeostasis. Additional analyses will explore the possible mechanisms of these results by identifying the systemic inflammation. Funding Sources: College of Human Sciences, Iowa State University Collaborative Seed Grant Program.